ANALISIS BUKTI PERMULAAN DALAM PENETAPAN TERSANGKA NARKOTIKA: STUDI KASUS PUTUSAN PRAPERADILAN NO. 14/PID.PRA/2023/PN JKT TIM: Analysis Initial Evidence In Determining Narcotics Suspects: Case Study Of Pretrial Decision No.14/Pid.Pra/2023/Pn Jkt Tim - Vira Felinda Ayu Cahyani; Setiyono (Reformasi Hukum Trisakti, 2025)
Based on sufficient preliminary evidence, Fahrul Roji as the applicant has been named a suspect by the BNN as the respondent. However, the applicant is dissatisfied with the determination because the evidence held by the respondent is considered insufficient. This study discusses the problem is the determination of preliminary evidence in determining a suspect in a narcotics case, with a case study of the pretrial decision No. 14 / PID.PRA / 2023 / PN JKT.TIM. The focus of the study is to analyze the types of valid evidence that can be used as the basis for sufficient preliminary evidence and the appropriateness of the judge's considerations in determining the suspect. The method used is normative study using secondary data and a descriptive approach analyzed qualitatively. Based on the discussion, it can be concluded and result that the preliminary evidence to determine the applicant as a suspect is insufficient, because the existing evidence is not accurate and only one can be accepted as valid evidence. Therefore, the applicant's request should be granted by the judge because there is no sufficient evidence for a narcotics crime.